An Elaborative Study on The Perception and Prevention of The East Javas PTKIN Students About Proxy War - Iffatin Nur; Munarji Munarji (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
As a new form of warfare, proxy war does not require arm contacts to invade a country. Through conspiracy, propaganda and the establishment, a country may be ravaged by other more powerful countries. As a developing country with abundant natural and human resources, Indonesia becomes an easy target for super power countries to launch their proxy wars. Therefore anticipatory measures to stem the dangers of a proxy war are needed. This study used a qualitative approach through interviews. The conclusions of this study are: (1) the perceptions ofthe East Java’s PTKIN students on the issue of proxy war. First, in terms of its notion, there are four perceptions about proxy war. Two of them do not have compatibility with the theory of proxy war. Second, the perception of the dangers of proxy war in which there are two perceptions: 1) that the proxy war is absolutely very dangerous and 2) that it cannot be justified simply to be dangerous or not before its victims arise. Third, in the constellation of proxy war, Indonesia has been for a long time in its vortex as Indonesia is a country with abundant natural and human resources.